2006
DOI: 10.1007/s10350-005-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics and Survival of Colorectal Cancer Between Japanese-Americans in Hawaii and Native Japanese in Japan

Abstract: In patients with colorectal cancer in Japanese-Americans in Hawaii, some of tumor characteristics have changed from those of native Japanese in Japan. However, there are no remarkable differences in prognostic factors and survival between the two groups. The present study suggests that certain changes of colorectal cancer characteristics that were seen in Japanese-American may occur in native Japanese in Japan in the near future, although the survival outcome of colorectal cancer may remain the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, the incidence of colon cancer in Japan has been increasing 27. In addition, CRC occurs more frequently in the proximal colon and less frequently in the rectum among the Japanese–American population in Hawaii compared to native Japanese in Japan 28. These facts suggest that different genetic and environmental factors contribute to the pathogenesis of rectal, distal and proximal colon cancer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the incidence of colon cancer in Japan has been increasing 27. In addition, CRC occurs more frequently in the proximal colon and less frequently in the rectum among the Japanese–American population in Hawaii compared to native Japanese in Japan 28. These facts suggest that different genetic and environmental factors contribute to the pathogenesis of rectal, distal and proximal colon cancer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients and tumor characteristics of JA or NJ have been changing to those of American people. Sakamoto et al [10] investigated whether characteristics, prognostic risk factors, and survival of CRC of JA in Hawaii are different from those of NJ in Japan from 1996 to 2002, and reported that there are no remarkable differences in prognostic factors and survival between the two groups. Kotake et al [11] reported that male patients of NJ with CRC have remarkably increased.…”
Section: Discussionmentioning
confidence: 97%
“…This tendency is consistent with the results of the hierarchical cluster analysis. However, a comparison of patient characteristics was made between the 1,129 Japanese patients with colorectal cancer in our study and the data from 30,002 patients who were registered with the Japanese Society for Cancer of the Colon and Rectum between 1993 and 1997 ( 41 ), as well as the data from 621 patients who were registered in a single institution in Japan between 1992 and 2002 ( 42 ). This comparison revealed that, although age, gender, tumor location and histology had generally similar distributions, the percentages of T1/2, N0 and stage I/II were clearly low, and as a whole, the stage of cancer tended to be more advanced in our study.…”
Section: Discussionmentioning
confidence: 99%